Doğu Akdeniz’de Deniz Yetki Alanlarının Sınırlandırılması Bağlamında Türkiye - Mısır İlişkileri - Gökhan Topçu; Pınar Yürür; Arda Özkan (Coğrafi Bilimler Dergisi)
The seas have been the scene of wars between major naval powers at different period of history. One of the most important results of these wars was the birth of maritime law. Over time, the demands of states regarding the use of the seas increased. As a result of such developments, the UNCLOS emerged in 1982 as a result of the conferences on the law of the sea. As a result of the expansion of the areas of activity in the seas and the increasing energy needs in the world, the importance of the Eastern Mediterranean, as in other strategic seas, has started to increase gradually. This situation has made the issue of the delimitation on the maritime areas in the region important and in this study, the relations between two important states of the region, Turkey and Egypt, are discussed in the context of maritime jurisdiction areas. The aim of the study is to provide an informative perspective and contribute to the determination of the suitable road map to be followed pro-actively in order to achieve results based on the equitable principles within the framework of the rights and interests of the two states. In the study, in which the content analysis method is used, it is predicted that the period in which political relationsbetween the states are re-established and open-door diplomacy is carried out will continue in a positive direction.